Metabolism and trophological status evaluation of patients with gastric cancer after gastrectomy and subtotal proximal resection of the stomach - Вінник, Юрій Олексійович; Трунов, Геннадій Віталійович; Абухассан, Мохамед Саєд Хуссейн (ScienceRise: Medical Science, 2016)
Aim. The indices of DT functional state and some indices of metabolism were studied and also trophological status of patients with gastric cancer after gastrectomy (GE) by the new technology of esophageal anastomosis formation was evaluated in the work. Methods. The research included 150 patients with gastric cancer. In the main group was applied the new technology of esophageal anastomosis formation. In 1, 12 and 24 months after gastroectomy (GE) the test on tolerance to glucose, carbohydrate load and, scatological study were carried out and the body mass index of patients was measured. The clinical data were analyzed using the program software for personal computer: Microsoft Excel et Statistica 6.0. Statictical processing was carried out using Student criterion. The differences were considered as reliable ones at p <0,05. The analysis of clinical data was carried out using the program software for personal computer: Microsoft Excel et Statistica 6.0. Result. It was established, that in patients of the main group during 2 years after resection of stomach was observed the decrease of number of complaints after carbohydrate load and manifestations of damping syndrome decreased in 2 times. With increase of postoperative term the creatorrhoea manifestations decreased in the main group. Patients with the new variant of reconstruction had better trophological status that is proved by the increase of body mass index. Conclusions. Thus, the use of the new method of reconstruction of digestive tract at GE significantly increases the trophological state, indices of carbohydrate metabolism and DT functional state in both postoperative and remote terms after GE